A Study Of Health Status Of Aged Persons In Slums Of Urban Field Practice Area, Bangalore - Niranjan G V; Vasundhra M K (Wolters Kluwer Medknow Publications, 1996)
Research Question: What is the health status of aged persons in urban slums? Objective: To study the health status of aged persons in urban slums and factors associated with it. Study Design: Cross-sectional. Participant: Persons aged 60 years and above. Setting: 11 Slums of Bangalore city. Sample size: 409 (223 males & 186 females) Study variables: Age, Sex, type of family. Marital status, occupation, social class, literacy status, addiction, and morbidity pattern, Results: Among 223 (54.52%) males and 186 (45.48%) females majority (46.21%) belonged to the social class-III. Only 25.19% of the were literate and 39.36% of the aged were engaged in active work. 90.46% of the aged had one or more addiction. Most of them (82.89%) were ill at the time of survey, cataract (72.95%) being the commonest caused of illness followed by anemia (12.59%). The problems due to socio-psychological causes were very minimal, probably because majority (88.75%) of them were residing with their families.